Physiochemical characteristics of soil in tropical sal (Shorea robusta Gaertn.) forests in eastern Nepal - Paudel, Shishir; Sah, Jay P (Himalayan Journal of Sciences, 2006)
The physiochemical properties of soils of two different types of forests (pure Shorea robusta and mixed Shorea robusta) were analyzed. Soil samples were collected from both types of forest and analyzed for texture, pH, organic matter, humus content, water holding capacity, nitrogen, phosphorous and potassium. In both the pure and mixed forest, soil was sandy loam (60.12% and 50.58% sand, 28.59% and 35.24% silt and 11.12 and 22.41% clay, respectively). The pH value was lower in pure forest (4.33) than in the mixed forest (5.26), and so were phosphorus and water holding capacity. The higher values of humus, organic matter, nitrogen and potassium (7.34%, 2.42%, 0.117%, 267.73 kg/ha, respectively) were found in pure forest. The higher levels of soil nutrients in the pure forest were due partly to reduction in the loss of top soil and partly to the increased supply of nutrients in the form of leaf litter and biomass from the larger number of sal trees and their saplings. Key words: Shorea robusta, soil texture, nitrogen, soil pH, Udayapur Himalayan Journal of Sciences 1(2): 107-110, 2003